Rhinovirus-Induced Cytokine Alterations With Potential Implications in Asthma Exacerbations: A Systematic Review and Meta-Analysis - Liew, Kong Yen; Koh, Sue Kie; Hooi, Suet Li; Ng, Matthew Kah Lup; Chee, Hui-Yee; Harith, Hanis Hazeera; Israf, Daud Ahmad; Tham, Chau Ling (Frontiers in Immunology, 2022)
Background: Rhinovirus (RV) infections are a major cause of asthma exacerbations. Unlike other respiratory viruses, RV causes minimal cytotoxic effects on airway epithelial cells and cytokines play a critical role in its pathogenesis. However, previous findings on RV-induced cytokine responses were largely inconsistent. Thus, this study sought to identify the cytokine/chemokine profiles induced by RV infection and their correlations with airway inflammatory responses and/or respiratory symptoms using systematic review, and to determine whether a quantitative difference exists in cytokine levels between asthmatic and healthy individuals via meta-analysis. Methods: Relevant articles were obtained from PubMed, Scopus, and ScienceDirect databases. Studies that compared RV-induced cytokine responses between asthmatic and healthy individuals were included in the systematic review, and their findings were categorised based on the study designs, which were ex vivo primary bronchial epithelial cells (PBECs), ex vivo peripheral blood mononuclear cells (PBMCs), and human experimental studies. Data on cytokine levels were also extracted and analysed using Review Manager 5.4. Results: Thirty-four articles were included in the systematic review, with 18 of these further subjected to meta-analysis. Several studies reported the correlations between the levels of cytokines, such as IL-8, IL-4, IL-5, and IL-13, and respiratory symptoms. Evidence suggests that IL-25 and IL-33 may be the cytokines that promote type 2 inflammation in asthmatics after RV infection. Besides that, a meta-analysis revealed that PBECs from children with atopic asthma produced significantly lower levels of IFN-β [Effect size (ES): -0.84, p = 0.030] and IFN-λ (ES: -1.00, p = 0.002), and PBECs from adult atopic asthmatics produced significantly lower levels of IFN-β (ES: -0.68, p = 0.009), compared to healthy subjects after RV infection. A trend towards a deficient production of IFN-γ (ES: -0.56, p = 0.060) in PBMCs from adult atopic asthmatics was observed. In lower airways, asthmatics also had significantly lower baseline IL-15 (ES: -0.69, p = 0.020) levels. Conclusion: Overall, RV-induced asthma exacerbations are potentially caused by an imbalance between Th1 and Th2 cytokines, which may be contributed by defective innate immune responses at cellular levels. Exogenous IFNs delivery may be beneficial as a prophylactic approach for RV-induced asthma exacerbations.